Kekhususan Tugas KPK dalam UU No.30 Tahun 2002 Dibandingkan Dengan Ketentuan Dalam Hukum Acara Pidana - Dharyanto, Ikang (Pelita Harapan University, 2004)
Corruption in Indonesia has become widely in the society. The existence through the years can be seen from the corruption cases that always occur and have resulted of the big losses of the economic demand. Besides that, we can also see from the quality of the criminal act which is done with a great and neat systems and also has came into the social life in a country. The raise of the corruption can bring a big destruction to the economic life in Indonesia. Corruption can be categorized as a criminal act that break the Â social rights and society economic rights. So that corruption can not be anymore categorized as normal crime. Thats why instead of the normal ways, to tight corruption a country should use the extra, ordinary method. The maintenance to fight the corruption which has already used the conventional ways was totally failed. Because of this there is a need to use a new method to fight the corruption, such as establishing an institution that has a special authority, and independence, like KPK (Komisi Pemberantasan Korupsi). Â KPK is a institution which has special authority and independence and free from the other institution authority. Hopefully with this institution the corruption in Indonesia can be gone forever.